Cultural Autonomy for Minorities in the Baltic States, Ukraine, and the Russian Federation: A Dead Letter (Polish Yearbook of International Law, 2016)
One of the direct results of the collapse of the former USSR was the emergence of centrifugal ethnic minority nationalisms, which posed a threat to the stability of the then newly-established (or restored in the case of the Baltic democracies) states. In this context, one of the mechanisms introduced by the leading elites in several countries (e.g. Latvia, Ukraine, Estonia, the Russian Federation) in order to address the minority diversity issue, ensure stability, and gain international support (in the case of the Baltic states) was a cultural autonomy scheme, which has its origins in the ideas of the late 19th century Austro-Marxist school of thought. This model was successfully implemented once in the past, in inter-war Estonia. However, its modern application, even in cases when it does not just remain on paper (such as in Latvia and Ukraine), seems to serve other motives (e.g. a restitutional framework in Estonia, control of the non-titular minority elites in Russia) rather than the satisfaction of minority cultural needs, thus making cultural autonomy a dead letter.